Negotiation and Internalization of Religious Moderation Values in Shaping Tolerance Among Generation Z Students in the Social Media Era: A Case Study of SMAN 5 Purworejo - Choirun Nisa; Mahmud Nasir (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
Amid the growing influence of digital environments on young people’s religious perspectives, understanding how Generation Z constructs and internalizes religious moderation values is increasingly important for fostering tolerance in plural educational settings. This study aimed to analyze how students construct their understanding of religious moderation, explain the processes through which these values are negotiated and internalized in the formation of tolerant attitudes, and examine the mediating role of social media at SMAN 5 Purworejo. Employing a qualitative case study design, data were collected through in-depth interviews, observations, and documentation. The data were analyzed using the interactive model of Miles, Huberman, and Saldaña, comprising data condensation, data display, and conclusion drawing, while credibility was established through source and technique triangulation. The findings indicate that students’ understanding of religious moderation is constructed through interactions among family, school, peers, and social media. Tolerant attitudes develop through value negotiation when students encounter diverse religious information in digital spaces and are subsequently internalized through Islamic Religious Education, teacher exemplarity, an inclusive school culture, and strengthened digital literacy. Social media does not directly determine students’ religious attitudes; rather, its influence is mediated by teachers, school culture, and students’ digital literacy. The study concludes that tolerance among Generation Z emerges from a dynamic process of negotiating and internalizing religious moderation values across formal education, social environments, and digital spaces. These findings contribute to the literature on religious moderation and digital socialization and highlight the importance of integrating teacher guidance, inclusive school practices, and digital literacy into educational strategies for strengthening tolerant attitudes among students.